Myotome meanderings: Cellular morphogenesis and the making of muscle - Hollway, Georgina E; Currie, Peter D (EMBO reports, 2003)
The formation of muscles within the vertebrate embryo is a tightly orchestrated and complex undertaking. Beyond the initial specification of cells to become muscle are several complex cellular movements and migrations, which lead to the positioning of muscle precursors at specific locations within the embryo. The consequent differentiation, elongation and striation of these cells results in the formation of individual muscles. Investigation of the in vivo morphogenesis of individual vertebrate muscle cells has only recently begun, and is being approached through the use of sophisticated cell labelling and lineage analysis techniques. However, a consensus about the mechanisms involved has yet to be achieved. This review outlines vertebrate embryonic muscle formation in chick, fish and mice, focusing on the embryonic myotome, which generates both the axial musculature and the appendicular muscle of the fins and limbs. We highlight the points of consensus about, and the complexity of, this developmental system, and propose an evolutionary context for the basis of these understandings.